Depression and Pain in Heart Transplant Recipients: An Observational Study. (January 2017) - Conway, Aaron; Sheridan, Judith; Maddicks-Law, Joanne; Fulbrook, Paul; Ski, Chantal F.; Thompson, David R.; Clark, Robyn A.; Doering, Lynn V.
Characterizing how physical and psychological symptoms interact in heart transplant recipients may lead to advances in therapeutic options. This study examined associations between pain and major depression. Method: A cross-sectional study was conducted with adult heart transplant recipients. Pain was measured with the bodily pain domain of the Short Form-36 Health Survey and psychological distress with the Kessler Psychological Distress Scale (K-10). The Mini International Neuropsychiatric Interview, version 6.0, was used to identify participants meeting the criteria for major depression. Hierarchical linear regression was used to determine if there was an association between pain and major depression, controlling for pharmacological treatment of depression, severity of psychological distress, and clinical characteristics including immunosuppression medication which may induce pain as a side effect. Results: Average pain score of the 48 heart transplant recipients was 43 ( SD ± 10, range 0–100, lower scores indicate worse pain), with moderate pain reported by 39% ( n = 19). Major depression was associated with worse pain ( R 2 change = 36%, β = −16, 95% confidence interval [CI] = [−30, −4], p = .012). Pharmacological treatment for depression was associated with better pain scores ( R 2 change = 1.5%, β = 13, 95% CI [4, 23], p = .006). Conclusions: Heart transplant recipients with major depression had worse pain after controlling for pharmacological treatment of depression, severity of psychological distress, and clinical characteristics. Thus, it is imperative that clinicians devising a treatment regimen for pain in heart transplant recipients take into account co-occurring depression and vice versa.